Relationship between attitude towards mathematics and mathematical problem-solving achievement among pre-university students in Malaysia - Abu Bakar, Suriati; Mohd Ayub, Ahmad Fauzi (Academy of Sciences Malaysia, 2020)
The purpose of this study was to identify the relationship between attitude towards mathematics and problem-solving achievement among pre-university students. The sample of the study consisted of 312 One-year Matriculation Programme students from three matriculation colleges. The Attitude Toward Mathematics Inventory (ATMI) and a mathematical test were used in data collection. The results indicated that students had a high level of attitude towards mathematics. Inferential analysis showed a significant positive relationship between overall attitude towards mathematics with mathematical problem-solving achievement. Four sub-factors, i.e., self-confidence, value, enjoyment and motivation were found to have positive significant relationship with problem solving achievement. As a result, from these findings, recommendations were identified for future research.